2020
DOI: 10.1155/2020/8219536
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis C Virus Infection in a Surgical Population of Southeast China: A Large-Scale Multicenter Study

Abstract: Background. Chronic HCV infection affects 80 million people globally and may progress to advanced liver disease. The present study aims to investigate the present epidemiology of HCV infection in a southeastern Chinese surgical patient cohort. Methods. Blood samples obtained from 78,484 surgical patients from 18 different city and county hospitals were enrolled. The incidence of serum HCV antibody positivity, HCV RNA load, and HCV genotyping, as well as demographics and relevant clinical history, were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…However, it was much higher than the rate of voluntary blood donors, which was 0.51% [14]. This study showed that the positive rate of anti-HCV was 0.92%, which is slightly higher than the 0.61% reported in the general population of China in 2009 [15]. Recent studies have shown that there are approximately 185 million infections worldwide, and the HCV seroprevalence rate has risen to 2.8% in the past decade [16].…”
Section: Discussionmentioning
confidence: 69%
“…However, it was much higher than the rate of voluntary blood donors, which was 0.51% [14]. This study showed that the positive rate of anti-HCV was 0.92%, which is slightly higher than the 0.61% reported in the general population of China in 2009 [15]. Recent studies have shown that there are approximately 185 million infections worldwide, and the HCV seroprevalence rate has risen to 2.8% in the past decade [16].…”
Section: Discussionmentioning
confidence: 69%
“…[ 29 ] In addition, some studies suggest that women have higher rates of viral clearance and a better response to HCV treatment than men. [ 30 ] HCV subtypes GT3a and GT3b are more prevalent in men than in women. However, the distribution of subtype GT2a in male carriers was much lower than that among women in this study (Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Different HCC risk factors show different prevalence rates between men and women, which may also contribute to apparent sex-related differences in HCC incidence. It has been reported that the prevalence rates for chronic HBV and HCV infection are over two times and 50% higher, respectively, in men (10.7% for HBV and 0.19% for HCV) compared to women (4.4% for HBV and 0.13% for HCV) in Southeast Asia [66,67]. In the US, incidences of HBV and HCV are also higher in men (3.5/10,000 for HBV and 0.8/100,000 for HCV) than in women (2.0/100,000 for HBV and 0.44/10,000 for HCV) (2016 US viral hepatitis surveillance; https://www.cdc.gov/hepatitis/statistics/2016surveillance/, accessed on 19 February 2021).…”
Section: Sex-dependent Dna Methylation Changes In Premalignant Liver Conditions Vs Hccmentioning
confidence: 99%